2016
DOI: 10.1371/journal.pone.0156452
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Polymeric Nanoparticles for Brain Delivery of High Molecular Weight Molecules in Lysosomal Storage Disorders

Abstract: Lysosomal Storage Disorders (LSDs) are a group of metabolic syndromes, each one due to the deficit of one lysosomal enzyme. Many LSDs affect most of the organ systems and overall about 75% of the patients present neurological impairment. Enzyme Replacement Therapy, although determining some systemic clinical improvements, is ineffective on the CNS disease, due to enzymes' inability to cross the blood-brain barrier (BBB). With the aim to deliver the therapeutic enzymes across the BBB, we here assayed biodegrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…Recently, a study demonstrated that biodegradable and biocompatible PLGA-nanoparticles modified with a 7-aminoacid glycopeptide (g7) were able to deliver a model drug (FITC-albumin) in MPS type I and II mice across the BBB. This result encourages experiments with enzyme-loaded g7-nanoparticles to the brain [73].…”
Section: Enzyme Delivery For Mps and Nanotechnologysupporting
confidence: 72%
“…Recently, a study demonstrated that biodegradable and biocompatible PLGA-nanoparticles modified with a 7-aminoacid glycopeptide (g7) were able to deliver a model drug (FITC-albumin) in MPS type I and II mice across the BBB. This result encourages experiments with enzyme-loaded g7-nanoparticles to the brain [73].…”
Section: Enzyme Delivery For Mps and Nanotechnologysupporting
confidence: 72%
“…This is ideal not only for proper activity of lysosomal enzymes but also to help restore lysosomal acidification, which is otherwise defective in LDs [117, 405]. PLGA nanoparticles targeted to intercellular adhesion molecule 1 (ICAM-1), discussed in Section 5.4, or by a small glycopeptide (g7), have been shown to significantly enhance transport of enzymes into the brain [406, 407]. In the latter case, albumin was used as a model protein and these nanoparticles were examined in animal models of MPS I and II [407].…”
Section: Additional Approaches Toward the Optimization Of Lysosomamentioning
confidence: 99%
“…PLGA nanoparticles targeted to intercellular adhesion molecule 1 (ICAM-1), discussed in Section 5.4, or by a small glycopeptide (g7), have been shown to significantly enhance transport of enzymes into the brain [406, 407]. In the latter case, albumin was used as a model protein and these nanoparticles were examined in animal models of MPS I and II [407]. As shown in Figure 3C, only g7-targeted PLGA nanoparticles, but not nanoparticles lacking g7 glycopeptide, were found in the brain of animals 2 h after intravenous administration [407].…”
Section: Additional Approaches Toward the Optimization Of Lysosomamentioning
confidence: 99%
See 1 more Smart Citation
“…The inorganic NPs embedded polymer matrix showed enhanced performance as discussed in a recent review dealing with preparation and characterization of cytocompatible multifunctional polymeric NPs by analyzing their fluorescence efficiency, the nature of the artificial cell-membrane structure, and their performance as in-cell devices [68]. In enzyme replacement therapy of lysosomal storage disorders (LSDs), using PLGA NPs modified with 7-aminoacid glycopeptide (g7) NPs along with high MW drug (FITC-albumin) improved the barrier crossing of albumin while delivering the drug to the brain [69].…”
Section: Polymeric Npsmentioning
confidence: 99%